Saggy skin as a presenting sign of angioimmunoblastic T‐cell lymphoma. (1st June 2016) - Maher, N. G.; Chiang, Y. Z.; Badoux, X.; Vonthethoff, L. W.; Murrell, D. F.
Summary: Angioimmunoblastic T‐cell lymphoma (AITL) is a rare, aggressive form of peripheral T‐cell lymphoma that has a variety of cutaneous manifestations. To our knowledge, saggy skin has not been documented as one of these manifestations. We report a case of a patient with angioimmunoblastic T‐cell lymphoma presenting initially with pruritus and saggy skin, which later progressed into erythroderma despite chemotherapy; the disease eventually resolved with autologous stem cell transplant. Appreciating the cutaneous manifestations of AITL may allow for earlier diagnosis and treatment.